2021
DOI: 10.3390/ijerph18041459
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship of Sitting Time and Physical Activity on the Quality of Life in Elderly People

Abstract: Few studies have shown the combined impact of sitting time and physical activity on quality of life in older people. This cross-sectional study, using data from the 2016–2018 Korean National Health and Nutrition Examination Survey, examines the association between sitting time and physical activity and health-related quality of life (HRQoL) in Korean adults aged ≥ 65 years. HRQoL was assessed using the EuroQol-5 Dimension (EQ-5D, three-level version). We divided subjects into groups based on sitting time and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 29 publications
2
14
0
Order By: Relevance
“…On the contrary, and as various research concluded, a sedentary lifestyle negatively affects health and consequently quality of life. This was the conclusion reached in a study conducted with a sample of 4276 older people [ 6 ]. In the same vein, 2 cross-sectional studies carried out with samples of 3201 and 3543 older people, respectively, showed that those who spent more time without practicing physical activity (more than 8 h a day in a sedentary state) had a poorer psychological, physical and social quality of life [ 7 ].…”
Section: Introductionsupporting
confidence: 55%
“…On the contrary, and as various research concluded, a sedentary lifestyle negatively affects health and consequently quality of life. This was the conclusion reached in a study conducted with a sample of 4276 older people [ 6 ]. In the same vein, 2 cross-sectional studies carried out with samples of 3201 and 3543 older people, respectively, showed that those who spent more time without practicing physical activity (more than 8 h a day in a sedentary state) had a poorer psychological, physical and social quality of life [ 7 ].…”
Section: Introductionsupporting
confidence: 55%
“…Studies have shown that the promotion of social participation among older individuals is a key factor in successful aging [ 46 , 47 ]. Social participation itself, which involves getting up and interacting with others, is a key characteristic of healthy aging [ 48 ]. However, as older adults advance in age, social participation changes.…”
Section: Introductionmentioning
confidence: 99%
“…The psychological effects of exercise in overweight or obese people are known [60]. Exercise alleviates symptoms of depression and anxiety and improves the quality of life [61][62][63].…”
Section: Discussionmentioning
confidence: 99%